2002
DOI: 10.1099/00221287-148-12-4035
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase Kic1 affects 1,6-β-glucan levels in the cell wall of Saccharomyces cerevisiae

Abstract: KIC1 encodes a PAK kinase that is involved in morphogenesis and cell integrity. Both over-and underexpressing conditions of KIC1 affected cell wall composition. Kic1-deficient cells were hypersensitive to the cell wall perturbing agent calcofluor white and had less 1,6-β-glucan. When Kic1-deficient cells were crossed with various kre mutants, which also have less 1,6-β-glucan in their wall, the double mutants displayed synthetic growth defects.However, when crossed with the 1,3-β-glucan-deficient strain fks1∆,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…In fact, some cell wall-related mutants that display a constitutive high level of Slt2 phosphorylation, such as gas1, ecm33, itc1, or rot2, have been shown to be hypersensitive to Calcofluor White, a compound that interferes with cell wall assembly in a similar way to Congo Red (4,38). In agreement with a role for MSG5 in modulating cell wall-related cellular signaling, this gene has recently been isolated as a multicopy suppressor of the Calcofluor White sensitivity of cells overexpressing KIC1, a gene encoding a protein kinase involved in cell wall integrity (39).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, some cell wall-related mutants that display a constitutive high level of Slt2 phosphorylation, such as gas1, ecm33, itc1, or rot2, have been shown to be hypersensitive to Calcofluor White, a compound that interferes with cell wall assembly in a similar way to Congo Red (4,38). In agreement with a role for MSG5 in modulating cell wall-related cellular signaling, this gene has recently been isolated as a multicopy suppressor of the Calcofluor White sensitivity of cells overexpressing KIC1, a gene encoding a protein kinase involved in cell wall integrity (39).…”
Section: Discussionmentioning
confidence: 97%
“…The kic1 gene is essential and its mutants show morphological defects and cell-wall alterations. The defects include thicker cell walls, cell lysis, F-actin changes at the bud neck and growth in unseparated chains or clusters, which indicate a separation defect (Sullivan et al, 1998;Vink et al, 2002). Several other genes have been identified that might contribute to the same regulatory pathway as Nak1/Orb3 because their deletion phenotypes are very similar to that of nak1/orb3.…”
Section: Discussionmentioning
confidence: 98%
“…The resistance has been attributed to changes in the mannoprotein layer (Vink et al, 2002), with a specific function for some of the cell-wall proteins (Van Der Vaart et al, 1995). In mutant scw4scw10, zymolyase resistance is not lost after deletion of CHS3.…”
Section: Discussionmentioning
confidence: 99%